Galactic cosmic ray propagation models using Picard. (September 2020) - Kissmann, R.; Thaler, J.; Reimer, O.
Abstract: We will give an overview of recent developments in numerical modelling of CR transport in our Galaxy with the PICARD code. Corresponding numerical models aim at reproducing CR spectra and also diffuse gamma-ray emission from the Galaxy by solving the cosmic-ray transport problem in a three-dimensional model of the Galaxy. We address the impact of different transport physics processes on the flux and distribution of diffuse Galactic gamma rays: we investigate CR transport using different cosmic-ray source distribution models ranging from smooth source distributions to localised sources related to high-energy gamma-ray observations. Additionally, we consider anisotropic cosmic-ray diffusion in an improved Galactic magnetic field model. The choice of changing the different transport parameters is most readily visible in the inverse-Compton channel, which shows features not present in commonly-used axisymmetric transport models.